Evidence of a bactericidal permeability increasing protein in an invertebrate, the Crassostrea gigas Cg-BPI - Gonzalez, Marcelo; Gueguen, Yannick; Destoumieux-Garzón, Delphine; Romestand, Bernard; Fievet, Julie; Pugnière, Martine; Roquet, Françoise; Escoubas, Jean-Michel; Vandenbulcke, Franck; Levy, Ofer; Sauné, Laure; Bulet, Philippe; et al. (Proceedings of the National Academy of Sciences, 2007)
A cDNA sequence with homologies to members of the LPS-binding protein and bactericidal/permeability-increasing protein (BPI) family was identified in the oyster Crassostrea gigas. The recombinant protein was found to bind LPS, to display bactericidal activity against Escherichia coli, and to increase the permeability of the bacterial cytoplasmic membrane. This indicated that it is a BPI rather than an LPS-binding protein. By in situ hybridization, the expression of the C. gigas BPI (Cg-bpi) was found to be induced in hemocytes after oyster bacterial challenge and to be constitutive in various epithelia of unchallenged oysters. Thus, Cg-bpi transcripts were detected in the epithelial cells of tissues/organs in contact with the external environment (mantle, gills, digestive tract, digestive gland diverticula, and gonad follicles). Therefore, Cg-BPI, whose expression profile and biological properties are reminiscent of mammalian BPIs, may provide a first line of defense against potential bacterial invasion. To our knowledge, this is the first characterization of a BPI in an invertebrate.